Efektivitas Self Assessment dan Peer Assessment Dalam Pembentukan Karakter Siswa - Anita Wijayanti (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Measurement of student attitudes can be done through self-assessment and peer assessment which is a component of assessment in Curriculum 2013. Therefore the researcher wants to show how much effectiveness of self-assessment and peer assessment to form the character of student. With the formulation of the problem as follows: How the implementation of self-assessment and peer assessment to be effective in shaping the character of students? The results of this study show that; Self-assessment and peer assessment that is part of the assessment of the 2013 curriculum is the most effective assessment technique in shaping the character of the students. The character can have a positive impact, and if a positive personality has been established (self-actualization) then intellectual development (knowledge and skills) will also increase. This can be applicable in all areas of learning and will contribute to understanding the concepts within it.